Eccentricity-Based Energies of Non-Commuting Graph for Dihedral Groups (European Journal of Pure and Applied Mathematics, 2025)
Spectral graph theory is a research topic that combines algebra and graph theory, with the intersection representing a graph as a matrix. The eigenvalues of the matrix give the value of graph energy. This research focuses on the non-commuting graph for dihedral groups corresponding to eccentricity-based matrices including eccentricity, sum eccentricity, and average degree eccentricity matrices.